2022
DOI: 10.1093/hmg/ddac067
|View full text |Cite
|
Sign up to set email alerts
|

Pregnenolone-methyl-ether enhances CLIP170 and microtubule functions improving spine maturation and hippocampal deficits related to CDKL5 deficiency

Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 (CDKL5) cause CDKL5 deficiency disorder (CDD), a neurodevelopmental disease characterized by severe infantile seizures and intellectual disability. The absence of CDKL5 in mice causes defective spine maturation that can at least partially explain the cognitive impairment in CDKL5 patients and CDD mouse models. The molecular basis for such defect may depend on the capacity of CDKL5 to regulate microtubule (MT) dynamics through its association with the MT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The presence of GABA A Rs on the neuronal membrane is determined by the dynamic balance of delivery, recycling and degradation, which altogether depends on complex regulatory mechanisms involving the interaction of various proteins, including gephyrin, with MTs [28,29]. We previously showed that various neuronal defects linked to CDKL5 deficiency in vitro and in vivo can be restored through treatment with PME, which promotes MT dynamics [13][14][15]. We therefore found it intriguing to analyse whether the treatment of Cdkl5-KO neurons with PME could restore the observed defects at the inhibitory synapse.…”
Section: Gabaergic Defects In Cdkl5-ko Neurons Are Normalised Upon Tr...mentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of GABA A Rs on the neuronal membrane is determined by the dynamic balance of delivery, recycling and degradation, which altogether depends on complex regulatory mechanisms involving the interaction of various proteins, including gephyrin, with MTs [28,29]. We previously showed that various neuronal defects linked to CDKL5 deficiency in vitro and in vivo can be restored through treatment with PME, which promotes MT dynamics [13][14][15]. We therefore found it intriguing to analyse whether the treatment of Cdkl5-KO neurons with PME could restore the observed defects at the inhibitory synapse.…”
Section: Gabaergic Defects In Cdkl5-ko Neurons Are Normalised Upon Tr...mentioning
confidence: 99%
“…By treating symptomatic Cdkl5-KO mice with PME, we previously found that CDKL5related hippocampal-dependent behavioural and excitatory synaptic defects benefit from increased MT dynamics in vivo [15]. Intrigued by the positive effect of PME on inhibitory synapses in vitro, we proceeded to evaluate its effect in vivo, also.…”
Section: Gabaergic Defects In Cdkl5-ko Neurons Are Normalised Upon Tr...mentioning
confidence: 99%
See 3 more Smart Citations